The timing of medical examination following an allegation of sexual abuse: is this an emergency?. Issue 10 (2nd May 2008) - Watkeys, J M; Price, L D; Upton, P M; Maddocks, A
Abstract : Aim: To ascertain the frequency of significant anogenital signs, at medical examination, following an allegation of sexual abuse, in relation to the timing of the examination. Method: A case series of 331 children, who were referred by the police or social services for examination, following an allegation of child sexual abuse or suspicion of this, over a 3½-year period in a defined geographical area. Results: Two hundred and fifty-seven children alleged penetrative abuse, of whom 114 were seen within 7 days of the abuse. Twenty-three children alleged penetrative anal abuse within the previous 7 days; 13 of these had abnormal findings (56.5%) compared with 9 (18%) of the 50 children seen more than 7 days after anal abuse. Ninety-two girls alleged penetrative vaginal abuse within the previous 7 days and of these 46 (50%) had abnormal findings, compared with 31 (30.7%) of the 101 girls seen more than 7 days after the alleged abuse. In addition 33 girls seen within 7 days had other signs associated with probable assault. Abnormal findings were more common in post-pubertal girls. Conclusion: Pubertal and post-pubertal girls are more likely to have significant genital signs if they are examined within 7 days of the last episode of sexual abuse. Our findings suggest that abnormal anal signs are more likely to be present in the acute phase. This study indicates that children should be examined as soon as possible following a referral. This will have implications for clinical practice. Regardless of the lack of accurate history it will always be important to examine the child as soon as possible after disclosure.